Retail Gasoline Trading Practices in Pematang Rahim Mendahara Ulu Village: An Islamic Business Ethics Perspective - Tugiyono; Kurniawan; Rayvin Domingo Pestaño (CV. Zabags Qu Publish, 2026)
This study is motivated by the widespread practice of retail gasoline trading in Pematang Rahim Mendahara Ulu Village, which has emerged as a community-based response to limited access to formal fuel distribution channels and pressing local economic needs. The research aims to examine these transactional practices through the lens of Islamic business ethics and Islamic economic law, with particular attention to contractual clarity (akad), price fairness, measurement transparency, and the potential presence of gharar (uncertainty). Employing a qualitative field-based approach with a case study strategy, data were collected through direct observation, in-depth interviews with retailers and consumers, and supporting documentation. The data were subsequently analyzed using thematic analysis techniques. The findings indicate that retail gasoline transactions operate informally and are largely grounded in interpersonal trust; however, several issues persist, including inconsistent measurement standards, price fluctuations, and concerns related to distribution legality. Conceptually, this study contributes to the development of Islamic economic ethics discourse within informal market settings and offers practical implications for strengthening ethical business literacy and improving local-level energy distribution governance.